PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR FISIKA MATERI LISTRIK DINAMIS DI KELAS IX SMP NEGERI 1 PADANGSIDIMPUAN - Purba, Arison (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2022)
This study aims to see: 1) how is the use of using cooperative learning of TPS type in the subject matter of dynamic elektricity in Class IX SMP Negeri 1 Padangsidimpuan; 2) how the description of the learning outcomes of students in the subject matter of Physics dynamic elektricity before and after using cooperative learning of TPS type in Class IX SMP Negeri 1 Padangsidimpuan; 3) Is there a significant relationship between using cooperative learning of TPS type to the learning outcomes of students in the subject matter of Physics dynamic elektricity in Class IX SMP Negeri 1 Padangsidimpuan. The method of this research is experimental by with 80 students as the sample. Observation and test are used in collecting the data. Descriptive and inferential analyzes are used to analyzed the data. Based on the data analysis, it was found that: a) the average of using cooperative learning of TPS type is 84,19 (very good category), b) the average of students’ Physics achievement on the topic of dynamic elektricity before using cooperative learning of TPS type is 61.9 (less category) and after using cooperative learning of TPS type is 85,5 (very good category), and c) tcount is greater than ttable (19,24>1.68). It can be concluded that there is the significant influence of using cooperative learning of TPS type on students’ Physics achievement on the topic of dynamic elektricity at the eleventh grade student of SMP Negeri 1 Padangsidimpuan.